Movement-voting nexus in hybrid regimes: voter mobilization in Hong Kong's Anti-Extradition Bill Movement. Issue 7 (3rd October 2022) - Fong, Brian C. H.
ABSTRACT: The "movement-voting nexus" thesis highlights the impact of transformative social movements on shifting voting behaviour and electoral outcomes. However, existing studies have overwhelmingly focused on the context of democracies. This study goes beyond the existing literature by testing the applicability of "movement-voting nexus' in the context of hybrid regimes, using the voter mobilization in the Hong Kong's Anti-Extradition Bill Movement as a case study. The findings of this study are two-fold: The quantitative findings from a territory-wide telephone survey validated the thesis of "movement-voting nexus' in Hong Kong's hybrid regime, statistically establishing the significance of "movement support" as a novel predictor of voting behaviour (vis-à-vis other predictors such as political partisanship) in times of transformative social movement, as in the case of democracies; the qualitative findings from extended interviews of survey respondents revealed that the "movement-voting nexus" was operating in the shadows of authoritarian electoral influence in the territory, reflecting the nuanced features of Hong Kong's hybrid regime. This study contributes to extant literature by advancing the discussion from democracies to hybrid regimes, paving the way for future research across diverse political regimes.